1994
DOI: 10.2166/wst.1994.0613
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution model for methanogenic granules from full scale UASB and IC reactors

Abstract: The size distribution of methanogenic granules from ten full scale UASB and Internal Circulation (IC) reactors were studied at regular time intervals. A size distribution model was developed based on these data and additional lab-scale experiments. Full scale data were used, since the hydrodynamic conditions in full scale reactors influencing the size distribution cannot be simulated properly in lab scale reactors. It was concluded that breaking and/or disintegration did not significantly contribute to the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 0 publications
1
20
0
2
Order By: Relevance
“…Initial experiments with the ASBR were conducted in 1989 and 1990 by Habben [47] and Pidaparti [113]. Since that time, the ASBR has been applied at laboratory scale to several different wastewaters, including starch wastewaters, furfuraldehyde wastewaters, landfill leachate, and swine wastes.…”
Section: The Analytical Laboratory Service and The Bessey Microscopy mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial experiments with the ASBR were conducted in 1989 and 1990 by Habben [47] and Pidaparti [113]. Since that time, the ASBR has been applied at laboratory scale to several different wastewaters, including starch wastewaters, furfuraldehyde wastewaters, landfill leachate, and swine wastes.…”
Section: The Analytical Laboratory Service and The Bessey Microscopy mentioning
confidence: 99%
“…In the majority of studies, granular biomass displays a higher SMA than that of non-granular biomass [30,33,34,87,113,114,135]. However, when comparing intact granule activity to disintegrated granule activity (whole granules broken apart by high shear or other procedure), it was found that the intact and disintegrated granules displayed similar SMAs.…”
Section: Activity Of Granular Biomassmentioning
confidence: 99%
“…There were two principle reasons about the above phenomenon [7] : (1) Gas lift function would be decreased when the energy consumption of internal circulation increased; (2) Massive gas did not outflow in time so as to increase the pressure in gas-collecting hood, which resulted in decreasing of pressure difference between the both sides of riser.The first IC reactor (1989) was built in DenBdsch of Netherlands, which volume and H/D was 970m 3 and 3 respectively [8] ; an IC reactor built in Doosendaal of Netherlands was used to treat chicory wastewater, which volume and H/D was 1100m which volume and H/D was 400m 3 and 4 respectively [10] . According to our simulation results, optimum value of H/D by calculating results was 3, which were very in accordance with above engineering practices.…”
Section: Correlation Between Qic and Biogas Productionmentioning
confidence: 99%
“…Factors affecting granule structure include wastewater type, reactor design and operational conditions (Kosaric et al, 1990;Pereboom, 1994;Schmidt and Ahring, 1996).…”
Section: Anaerobic Granulesmentioning
confidence: 99%